Toward Arab-Israeli peace : report of a study group - Brookings Study Group on Arab-Israeli Peace (Washington, D.C. : Brookings Institution, 1988)
This book is a report of a study group called the Brookings Study Group on the activities of the United States towards restoring peace between Arab and Israel
Report of the Brookings Study Group on Arab-Israeli Peace.
gp. 21/01/2019
loan
Keywords: Arab-Israeli conflict; Arab-Israeli conflict